Types of Employees’ Loyalty vs. Job Satisfaction (IT Company Case Research) - Hulbój, Marta (Edukacja Ekonomistów i Menedżerów, 2012)
The subject of the article is the connections between loyalty and job satisfaction based on surveys questionnaire conducted in a company of telecommunications industry. At the beginning workers were identified by type of loyalty presented by them. One can distinguish among them persons with a positive attitude, indifferent or negative. Then the types of job satisfaction and its determinants were presented. The results of research on the impact of job satisfaction, compared with the types of loyalty of tested employees were presented and discussed in the final part of the article.